LED audio illustrator / Salman Ayassy Razman & Muhammad Arif Farhan Muhammad Harith Fadzillah - Razman, Salman Ayassy; Muhammad Harith Fadzillah, Muhammad Arif Farhan (2015)
This project is about designing a board with full LEDs that can visualize and illustrate an audio signal. The tittle of the project is "LED audio Illustrator". This project works by having an audio input with threshold LED indicators we will be able to detect and estimate the level of sound pollution in an area. The audio levels in an area can be segregated and illustrated by the set level of threshold to correspond to the LED color variations. We use Arduino to store the command. By using Arduino so command can be easier to program. About this project, this device can also be implemented in a library to remind students of their audio levels to not exceed a certain limit to not bother other patrons of the library or any place where quietness is a key characteristic of a certain area. Basically this project runs with the help of a very important component which are Arduino. Therefore this project is meant to design and arrange a set of LED to put on a show by utilizing an input of either microphone or analog signal of some kind. These signals will then be evaluated by a program to be translated to the grid of LED.